Proceedings of the 20th ACM International Conference on Intelligent Virtual Agents 2020
DOI: 10.1145/3383652.3423882
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Predictability of Gesture Parameters from Speech and their Perceptual Importance

Abstract: Gesture behavior is a natural part of human conversation. Much work has focused on removing the need for tedious hand-animation to create embodied conversational agents by designing speechdriven gesture generators. However, these generators often work in a black-box manner, assuming a general relationship between input speech and output motion. As their success remains limited, we investigate in more detail how speech may relate to different aspects of gesture motion. We determine a number of parameters charac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 34 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…15 One problem for machine learning approaches is the nondeterministic relationship of speech and gesture; a plethora of valid gestures can and do occur for a given utterance, hence modeling cospeech gestures as exact joint positions or angles may be too constrictive to capture natural variety. Recent work instead proposes modeling the speech-gesture relation with higher-level parameters; Ferstl et al 1 propose a set expressive gesture parameters, namely, velocity, initial acceleration, gesture size, arm swivel, and hand opening, and show they can both be estimated from speech as well as perceptually impacting speech-gesture match. In a preliminary study, replacing GT gestures with parameter-matched gestures of similar length was shown to outperform unmatched gestures.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…15 One problem for machine learning approaches is the nondeterministic relationship of speech and gesture; a plethora of valid gestures can and do occur for a given utterance, hence modeling cospeech gestures as exact joint positions or angles may be too constrictive to capture natural variety. Recent work instead proposes modeling the speech-gesture relation with higher-level parameters; Ferstl et al 1 propose a set expressive gesture parameters, namely, velocity, initial acceleration, gesture size, arm swivel, and hand opening, and show they can both be estimated from speech as well as perceptually impacting speech-gesture match. In a preliminary study, replacing GT gestures with parameter-matched gestures of similar length was shown to outperform unmatched gestures.…”
Section: Related Workmentioning
confidence: 99%
“…Accompanying this work, we will release our full database of gestures, together with their values for the five expressive parameters, and corresponding speech. 1 We also release the five trained speech-to-parameter models for reproducibility (step 4 in Figure 1). We think this database will be a valuable resource for gesture research.…”
Section: Gesture Databasementioning
confidence: 99%
See 3 more Smart Citations